2002
DOI: 10.1023/a:1020685727460
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Morphologic analysis of geographic strains of Musca domestica carried out on natural and laboratory experiments starting with 400 and 800 eggs showed phenotypic variations related with latitude. Females of the natural populations showed clines for several morphological traits of the wing, whereas male flies showed a reduction in the dispersion measures (s2 and CV) of wing width and length. The same reduction was obtained for males, females and total number of flies of the natural populations in dispersion of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 27 publications
0
18
4
Order By: Relevance
“…in these two species (Cavicchi et al, 1985;Partridge et al, 1994a;James et al, 1995;van't Land et al, 1999;Zwaan et al, 2000;Navarro-Campos et al, 2011) and the general trend that insects develop larger body sizes and wings in at lower temperatures (Bergmann, 1847;Ray, 1960). A previous study of natural M. domestica populations in South America found a positive correlation between latitude and wing size in females (Alves and Bélo, 2002). Since such latitudinal clines are often related to variable temperatures, the complete lack of association between wing size and rearing temperature in our work is a bit surprising.…”
Section: Plasticity In Response To Rearing Temperaturementioning
confidence: 46%
See 2 more Smart Citations
“…in these two species (Cavicchi et al, 1985;Partridge et al, 1994a;James et al, 1995;van't Land et al, 1999;Zwaan et al, 2000;Navarro-Campos et al, 2011) and the general trend that insects develop larger body sizes and wings in at lower temperatures (Bergmann, 1847;Ray, 1960). A previous study of natural M. domestica populations in South America found a positive correlation between latitude and wing size in females (Alves and Bélo, 2002). Since such latitudinal clines are often related to variable temperatures, the complete lack of association between wing size and rearing temperature in our work is a bit surprising.…”
Section: Plasticity In Response To Rearing Temperaturementioning
confidence: 46%
“…In line with these different behaviors, our interspecific PCA separated C. capitata and D. melanogaster (courtship songs) from M. domestica (mating strike) along PC2 that explained about 20% of the shape variation and captured differences in the ratio of wing width and wing length. Hence, the longer and narrower wings of M. domestica might be under selection for better flight performance (Alves and Bélo, 2002;Shyy et al, 2013), while the shorter and rounder wings of D. melanogaster and C. capitata seem to be better suited to displace more air for repeated buzzing (Burk and Webb, 1983;Webb et al, 1983;Wheeler et al, 1988;Talyn and Dowse, 2004;de Souza et al, 2015). Despite this potential link between interspecific wing shape differences and mating behavior, our data revealed that all three species were equally separated along PC1 that captured wing width along the proximal-distal axis and explained about 77% of the variation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This confirms earlier studies concerning other insects (Gaston and O’Neill 2004). In Diptera, the wing measurements were used successfully for the quantification of both within and between species variations (Brown 1980; Klingenberg et al 1998; Alves and Bélo 2002; Hall et al 2014; Siomava et al 2016). The wing venation differs markedly between Diptera species, and it can be used for identification of mosquitoes (Dujardin 2011; Sumruayphol et al 2016), tephritid flies (Van Cann et al 2015), tsetse flies (Kaba et al 2016), screwworm flies (Lyra et al 2010), and stable flies (Changbunjong et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that male M. domestica wings were slightly elongated compared to female wings, additionally increasing the moment of inertia and required inertial power. Therefore, in accordance with the “mating strike” behavior in flight, M. domestica wings may be less suited for buzzing, but their wing shape might be under selection for better flight performance, that is facilitated by long and narrow wings (Alves and Bélo, 2002).…”
Section: Discussionmentioning
confidence: 99%